Microbial community analysis in upflow anaerobic sludge blanket for the treatment of palm oil mill effluent - Sim, Lin Lin (2005)
Palm oil mill effluent (POME) has been treated using various technologies, yet not many of them provide a solution for waste degradation. Microbial community structure of the waste was not fully understood. In this study, the characteristics of POME were determined. The relation of pH, total suspended solids, total volatile solids and chemical oxygen demand of POME were studied. BLASTN and RDPII online-database were used to assess microbial community analysis. Acid-formers, methane-formers and fungal isolates were expected to be contributing to the treatment of POME. The relationship among microbial community members was studied. None of a single microbe was able to perform an effective POME treatment. A mixed culture of archaea, bacteria and fungus were essential to degrade the POME to an acceptable standard.